Structural Biology in the Clouds: The WeNMR-EOSC Ecosystem - Honorato, Rodrigo V.; Koukos, Panagiotis I.; Jiménez-García, Brian; Tsaregorodtsev, Andrei; Verlato, Marco; Giachetti, Andrea; Rosato, Antonio; Bonvin, Alexandre M. J. J. (Frontiers in Molecular Biosciences, 2021)
Structural biology aims at characterizing the structural and dynamic properties of biological macromolecules with atomic details. Gaining insight into three dimensional structures of biomolecules and their interactions is critical for understanding the vast majority of cellular processes, with direct applications in health and food sciences. Since 2010, the WeNMR project (www.wenmr.eu) has implemented numerous web-based services to facilitate the use of advanced computational tools by researchers in the field, using the high throughput computing infrastructure provided by EGI. These services have been further developed in subsequent initiatives under H2020 projects and are now operating as Thematic Services in the European Open Science Cloud (EOSC) portal (www.eosc-portal.eu), sending >12 millions of jobs and using around 4000 CPU-years per year. Here we review 10 years of successful e-infrastructure solutions serving a large worldwide community of over 23,000 users to date, providing them with user-friendly, web-based solutions that run complex workflows in structural biology. The current set of active WeNMR portals are described, together with the complex backend machinery that allows distributed computing resources to be harvested efficiently.